2018
DOI: 10.4995/wrs.2018.7547
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: Assessment of the better location of gnawing sticks in growing rabbit cages

Abstract: <p>The present work tries to determine the best location of wooden sticks for environmental enrichment, considering usage and level of contamination as variables. A total of 540 rabbits at 4 wk of age were caged in 60 groups of nine animals in conventional rabbit cages, and the effect of the allocation of wooden sticks was studied by fixing them on the floor in 30 cages and on the cage ceiling in the other 30 cages. The sticks were sampled during the fattening period (5 wk) to evaluate the contamination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Therefore, incorrect positioning of gnawing material, high stocking densities or social tension hindering movement towards the enrichment, and competition are potential additional hazards for the inability to express gnawing behaviour. Little is known about this, although growing rabbits consumed more of their gnawing stick if it was floor mounted rather than ceiling mounted (Marin et al, 2018) and when lactating does spent more time on their platform later in lactation (presumably to avoid their kits) they also used the enrichment mounted above the platform more often (Rommers et al, 2014b). Since younger rabbits gnaw more than older ones (Katsarou et al, 2011), the impact of a lack of suitable material may be greater for them.…”
Section: Inability To Express Positive Social Interactionsmentioning
confidence: 99%
“…Therefore, incorrect positioning of gnawing material, high stocking densities or social tension hindering movement towards the enrichment, and competition are potential additional hazards for the inability to express gnawing behaviour. Little is known about this, although growing rabbits consumed more of their gnawing stick if it was floor mounted rather than ceiling mounted (Marin et al, 2018) and when lactating does spent more time on their platform later in lactation (presumably to avoid their kits) they also used the enrichment mounted above the platform more often (Rommers et al, 2014b). Since younger rabbits gnaw more than older ones (Katsarou et al, 2011), the impact of a lack of suitable material may be greater for them.…”
Section: Inability To Express Positive Social Interactionsmentioning
confidence: 99%
“…As for the use of the different areas of the park, in the present trial, rabbits spent 51.5% observation time in the resting area; they rested for 39.0% of observation time in the resting area and spent 26.7% observation time in the feeding area (averages of the two observation days). Morisse et al [29] also showed that rabbits prefer to rest in the area of the park away from the feeders, likely because of less disturbance due to the animals' access to feeders. Based on this preference, we also provided the resting area with a plastic floor, which has been proven to be preferred over a wire net by rabbits [30][31][32].…”
Section: Effect Of Gnawing Blocksmentioning
confidence: 99%
“…Moreover, this type of enrichment also leads to hygienic problems, especially when wooden sticks are used. As a consequence, there is a recommendation to fix the sticks on the walls or the ceiling of the cage instead of the floor, in order to avoid an undesirable contamination of the sticks by pathogenic microorganisms that could cause the animals severe illnesses [29].…”
Section: New Models/trends In Housing Systems For Breeding Does 41 Individual Systems With Improved Environmentsmentioning
confidence: 99%